The layout of submerged horizontal plate breakwater (SHPB) with respect to the tidal-level variation. Issue 3 (3rd July 2018) - He, Ming; Xu, Wanhai; Gao, Xifeng; Ren, Bing
ABSTRACT: The submerged horizontal plate is widely regarded as an open-type breakwater and shows a sensitivity to tidal-level variation. However, nearly all existing studies assume a constant water level, which is deviated from the real situation. The present work conducts the pioneer investigation on the layout of the submerged horizontal plate breakwater (SHPB) with respect to tidal-level variation. It is carried out by using the smoothed particle hydrodynamics (SPH) method. A novel multilayer dynamic boundary particles (DBPs) technique is proposed for implementing the thin-wall boundary condition of the plate, accompanied by the approach of wave force calculation. A dam-break impact problem is first used to verify the multilayer DBPs technique. Then an experiment concerning solitary wave incidents on a submerged horizontal plate is numerically reproduced. Good agreements between the calculated and experimental wave profiles, hydrodynamic pressures, and wave forces are obtained. By applying the well-validated model, the effect of tidal-level variation on hydrodynamic characteristics of the SHBP, including the wave transmission coefficient, the pressure and velocity fields and the wave force, are investigated. On that base, the suggested layout of the SHBP with respect to the tidal range is given.